Inflammatory bowel disease diagnosis and therapeutics - Cohen, Russell D. (Clinical gastroenterology., 2011)
This Second Edition of Inflammatory Bowel Disease: Diagnosis and Therapeutics, provides readers with the most up-to-date approaches to IBD states, expansion of biological agents of treatment, new studies in the epidemiology of IBD, the changing economics of IBD, major advances in novel readiographic techniques; which aid in the detection of colorectal cancer in patients with IBD and new findings in the genetics of IBD. Major breakthroughs in new endoscopic evaluations of the bowel (i.e. Capsule endoscopy, double-balloon enteroscopy, endoscopic ultrasound) and their use in the inflammatory bowel diseases is also summarized in this book. This new edition continues to provide readers with a concise, yet in-depth review of many of the important areas in history, epidemiology, pathogenesis, diagnosis, and treatment of the inflammatory bowel diseases (ulcerative colitis and Crohn's disease), as well as associated issues: extra intestinal manifestations, ostomy care, women's issues and economics.